Effect of Self-transcendence, Self-distancing, and Family Functionality on Self-care Agency in Older Adults - Medina-Fernández, Josué; Orozco-González, Claudia Nelly; Torres-Soto, Nissa Yaing; Cortes-Montelongo, Diana; Yam-Sosa, Antonio; Medina-Fernández, Isaí (Investigación y Educación en Enfermería, 2024)
Objective. To determine the effect of self-distancing, self-transcendence, and family functioning on self-care agency in Mexican older adults. Methods. Correlational-explanatory design, with a sample of 253 elderly, collecting data through a simple random sampling. A personal data questionnaire was applied, the scale of: self-transcendence, the self-distancing subscale, the family APGAR and the ability to self-care in Mexican population from different demographic groups. Descriptive and inferential statistics were applied (Mann-Whitney U and a structural equation model) and the study was approved by a registered ethics committee. Results. The study had participation from 253 elderly, with a mean age of 68.02 years, with prevalence of the female sex (60.1%); the level of education was primary school or lower (51.4%). It was observed that the group of chronic diseases had lower self-distancing (U = 4.449.5, p = 0.038) and greater self-transcendence (U = 4177.0, p = 0.008), and selfcare (U = 4365.5, p = 0.024) than the group without chronic diseases. It was also found that self-transcendence, self-distancing, and family functionality produce a positive effect of 37% on selfcare. Conclusion. Self-distancing, self-transcendence, and family functionality explain an important proportion of selfcare in the elderly. Said knowledge permits understanding the care behavior of the elderly and, thus, propose future educational interventions by nursing to prevent or avoid functional, cognitive loss and social effects.